EFFECT OF OCCUPATIONAL SAFETY, OCCUPATIONAL HEALTH, AND WORK ENVIRONMENT ON WORK PRODUCTIVITY AT PT. PEPUTRA MASTERINDO, TAPUNG DISTRICT - Karsilah Karsilah; Syamsul Bahri; Yulizar Yulizar (STIE Bangkinang Publishing, 2022)
This research was conducted at PKS PT. Peputra Materindo, Tapung District in 2021. This study aims to determine the effect of occupational health, work safety and work environment on work productivity. The population in this study were all PKS PT. Peputra Materindo, Tapung District, which amounted to 148 people, and the sample used the slovin method so that the sample used was 62 people using multiple linear regression analysis. In discussing this research, the writer uses quantitative descriptive analysis, namely tabulating data from questionnaires and drawing conclusions quantitatively. The results of this study conclude that there is a simultaneous significant effect of the variables of occupational health, work safety and work environment on work productivity at PKS PT. Peputra Materindo Tapung District, There is a partially significant effect of the safety and work environment variables on work productivity at PKS PT. Peputra Materindo, Tapung District, The relationship between the variables of the influence of occupational health, work safety and work environment on work productivity is 67.0% with a very high contribution level relationship while the remaining 33.0% is influenced by other variables.